2021
DOI: 10.3390/medicina57050417
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Psychometric Properties of the Lithuanian Version of the Majeed Pelvic Score

Abstract: Background and Objectives: There are no valid patient-based pelvic ring function assessment tools in Lithuania. The most widely used instrument is the Majeed Pelvic Score (MPS), which is proven to be an effective tool for assessing pelvic function after pelvic injuries. The aims of our study were: (1) the translation and cross-cultural adaptation of the MPS for the Lithuanian-speaking population, (2) to test the psychometric properties of the Lithuanian version of the MPS (MPS-LT) at follow-up two-time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We found a signi cant ceiling effect (over 15%) in all domains of the translated MPS, in accordance with the existing literature [21,23,27,29]. This ceiling effect has been shown by Brouwers et al [31] to be present already 3 months after injury.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found a signi cant ceiling effect (over 15%) in all domains of the translated MPS, in accordance with the existing literature [21,23,27,29]. This ceiling effect has been shown by Brouwers et al [31] to be present already 3 months after injury.…”
Section: Discussionsupporting
confidence: 92%
“…Busso et al [27] reported a ceiling effect of the overall questionnaire at a minimum of 5 years of follow-up. Petryla et al [23] observed that ceiling effect wasn't present 2 months after injury, while it appeared in a second evaluation at 12 months. This may be explained by muscle repair and bone healing and their in uence on pain, physical activity and walking performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations